Analysis of Wages and Severance Pay During the Covid-19 Pandemic Reviewed from Labor Law - Emi Wakhyuni; Siti Nurhayati; Abdi Setiawan (Ilomata International Journal of Management, 2022)
The Corona Virus Disease 2019 pandemic was first discovered in the city of Wuhan, China at the end of December 2019. This virus spreads very quickly and has spread to almost all countries, including Indonesia. As a result of the spread of the Corona virus, it has a negative impact on several sectors such as the economic sector, business, tourism, industry, health and so on. The tourism sector has been hit hard by the Covid-19 pandemic. Until now, almost all tourist destinations in Indonesia are closed. This is a very difficult condition, in Indonesia almost all tourist destinations, hotels, facilities, and entertainment are closed and are only allowed for 50% of visitors based on Government recommendations. The Karo Regency Government is also facing the same problem, one of the sectors that is relied upon to support Karo Regency's Original Regional Revenue (PAD) is from the tourism sector, and Brasatagi Subdistrict is one of the sub-districts that is the mainstay of the tourism sector in Karo Regency. Speaking of the tourism sector, the industry that is most closely related is Hotels and Restaurants. Throughout 2020 until mid-2021, the hotel occupancy rate in the Brastagi District fell by almost 90%. The very significant decline in the level of tourist visits, hotel occupancy and restaurant visitors in Brastagi District has caused entrepreneurs of tourist sites, hotels and restaurants to suffer huge losses. Employers are no longer able to cover all operational costs, including the cost of wages for workers. This forces employers to rearrange their working hours and calculate the number of workers that they still allow them to employ. Some of this is done by applying alternate vacations or leave to their employees, some of them who are no longer able to survive, are forced to lay off temporarily, cut wages. or terminate the employment of its employees. The findings in this study are that employers are still required to pay wages in full in the form of basic wages and fixed allowances as long as workers are laid off during the COVID-19 pandemic and are required to provide severance pay for workers who have been laid off in accordance with Article 156 of Law No. 2003 concerning Manpower and the Ninth Part, Article 37 concerning Payment of Wages in a State of Bankruptcy in the Government Regulation concerning Wages no. 78 of 2015.